082. Ectopic Meningothelial Meningioma of the Soft Palate – A Rare Case Report - Sepa, Krenni; Setiawan, I Gede Budhi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p082, 2024)
Background : Ectopic meningiomas are rare neoplasms that occur entirely outside the intracranial and account for only 1–2% of all meningiomas. These tumors have been reported at various sites, however they are predominantly observed in the head and neck region. This study aims to document and analyze a rare case of ectopic meningothelial meningioma of the soft palate. Case: A 52-year-old woman who presented with a complaint of a lump in the roof of her mouth that had appeared five months prior. Examination of the local status through bimanual palpation revealed a mass in the soft palate extending to the oropharynx, displacing both the uvula and the anterior and posterior pillars. On imaging showed a solid, heterogeneous mass with central necrosis located in the right soft palate, extending into the oropharynx. The patient underwent a wide excision, which included ligation of the external carotid artery. Histopathology exams revealed an ectopic meningothelial meningioma. Conclusion: The diagnosis of ectopic meningioma may difficult due the occurrence in uncommon sites. The prognosis for tumours of the palate varies widely, depending on specific factors such as histology, tumor’s grade, margin status, cervical metastasis, and recurrence.